The evolution of marketing communication - Dalmé Mulder (Communicare)
Marketing communication is not a new phenomenon. Communication has been part of the marketing process for as long as people have exchanged goods. However, the advent of technology and research, among other reasons, has made the marketing communication process increasingly sophisticated in recent decades and has given rise to integrated marketing communication (IMC) and the integrated communication phenomenon. To understand this new approach to marketing communication, one has to go back to the roots thereof and scrutinise the path of development. “Innovation begins with abandonment. It’s not what you start; it’s what you stop that counts”, says Drucker (as quoted in Schultz, Tannenbaum & Lauterborn, 1994:1). This statement underlines the importance of knowledge about the development of marketing communication in order to understand the importance and effective application of this new approach called integrated communication. In this study historical research was conducted to seek out the implications of, and/or relationships between, approaches in marketing communication from the past and their connections with the present. The paper explores the different phases that occurred in the development of marketing communication from a mass communications focus in the 1960s to the integrated communications imperative of the present. It became apparent that integrated communication, which envelops integrated marketing communication, is crucial to an organisation’s overall success.